REVOLUSI PEMERINTAHAN, SUDAHKAH BEREVOLUSI? KOLOKASI ADJEKTIVA KATA “INDONESIA” DALAM COCA DAN COHA PADA PERIODE PEMERINTAHAN ORDE LAMA, ORDE BARU DAN ERA REFORMASI - Almira Fidela Artha (Department of Master of Linguistic, Universitas Airlangga, 2018)
Historically, Indonesia's system of government is divided into three periods, namely The old order, The new order and Reformation. Every government order has a different and changing image of the nation. This change can be analyzed by looking at the collocation of adjectives attached to the word